Effect of process parameters on wall thinning of high strength 21-6-9 stainless steel tube in numerical control bending. Issue 2 (April 2021) - Fang, Jun; Ouyang, Fang; Lu, Shiqiang; Wang, Kelu; Min, Xuguang
Abstract: Wall thinning, as one of the key defects determined directly the usability of the bent tube, should be strictly controlled. Elastic modulus changes with the plastic deformation and its influence the plastic forming quality of tube bending. To precisely predict the wall thinning of tube bending, a finite element (FE) model for numerical control (NC) bending of high strength 21-6-9 stainless steel tube (21-6-9-HS tube) was established considering the variation of elastic modulus. Using the model, the effects of process parameters on wall thinning of the 21-6-9-HS tube in NC bending were investigated. The results show that the variation of elastic modulus has no obvious effect on the change tendency of the wall thinning degree, but only increases the value of the wall thinning degree. The wall thinning degree enhances sharply at first, then occurs a platform deforming characteristics, and finally reduces abruptly from the bending section to the initial bending section, and it increases with the increase of the clearance of tube-bending die, the friction coefficient of tube-bending die and the friction coefficient of tube-wiper die or with the decrease of the clearance of tube-wiper die, but the increased degree is not significant in all conditions.